Multifarious Perspectives of Robert Burns’ Poetry: Exploring the Multifaceted Poetry of Robert Burns (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Robert Burns occupies a significant place in the History of English Poetry. He has been studied from different perspectives, but no detailed study of his social philosophy has been made so far. He has a tendency to weave his personal moods and experiences into the texture of his poems so that they become a mirror of the bundle of contradictory traits in his complex personality. He is regarded as an ‘untutored peasant’ on the one hand and venerated as a ‘social and literary rebel’ on the other. This paper explores the various aspects of Burns’ ideas and art in their comprehensiveness rather than in isolation. Some of the major aspects of his poetry chosen for the purpose are his sensibility, radicalism and realism, frustration and disappointment and his bucolic humour as a challenge to the opposing forces. The present paper attempts to fill up a gap in the criticism of Burns poetry by highlighting certain important aspects of his poetry. An attempt has been made to present a deeper insight into the creative process of Burns.